Relationship of fibroblast growth factor 21 with kidney function and albuminuria: multi-ethnic study of atherosclerosis. Issue 6 (15th May 2018) - Anuwatmatee, Sahapab; Allison, Matthew A; Shlipak, Michael G; McClelland, Robyn L; Kramer, Holly; Tang, Shudi; Hou, Liming; Rye, Kerry-Anne; Ong, Kwok Leung
Abstract: Background: Fibroblast growth factor 21 (FGF21) may play a role in the development of chronic kidney disease (CKD). We therefore investigated the relationship of plasma FGF21 levels with kidney function and albuminuria in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: The analysis included 5724 MESA participants ages 45–84 years between 2000 and 2002, free of clinically apparent cardiovascular disease (CVD). Participants were followed up in person at four additional clinic visits over 10 years. Plasma FGF21 levels were measured at baseline examination by enzyme-linked immunosorbent assay. Kidney function was assessed by estimated glomerular filtration rate (eGFR). Outcomes were urinary albumin:creatinine ratio (UACR) progression, incident CKD by eGFR (reaching eGFR <60 mL/min/1.73 m 2 with eGFR loss rate ≥1 mL/min/1.73 m 2 per year) and rapid kidney function decline (eGFR decline >5%/year). Results: At baseline, higher FGF21 levels, assessed as both continuous and categorical quartile variables, were significantly associated with lower eGFR and higher UACR, after adjusting for demographic, socioeconomic and other confounding factors [adjusted mean differences of −2.63 mL/min/1.73 m 2 in eGFR and 0.134 in log normally transformed UACR (mg/g) for the highest FGF21 quartile compared with the lowest quartile, all P < 0.001]. However, in longitudinal analyses, baseline FGF21 levels did not predict incident CKD by eGFR, rapid kidney function decline or UACR progression. No significant interaction with sex and race/ethnicity was found (all P > 0.05). Conclusions: Our study does not support a role of FGF21 as a biomarker for predicting kidney function decline or albuminuria in adults free of clinically apparent CVD at baseline.